GE11-PDA-Pt@USPIOs nano-formulation for relief of tumor hypoxia and MRI/PAI-guided tumor radio-chemotherapy. (12th March 2019) - Yang, Chengcheng; Mi, Xuan; Su, Huilan; Yang, Jingxing; Gu, Yiyun; Zhang, Lu; Sun, Wenshe; Liang, Xiaowen; Zhang, Chunfu
Abstract : GE11-PDA-Pt@USPIOs can relieve tumor hypoxic conditions efficiently and are highly effective for radio-chemotherapy of EGFR-positive tumors. Abstract : Radio-chemo combination therapy has synergetic therapeutic effects on tumors. However, the tumor microenvironment, e.g. hypoxia and elevated H2 S levels, limits its treatment efficacy. In this study, we developed a cisplatin-loaded, poly dopamine-coated and GE11 peptide-conjugated multi-functional theranostic system (GE11-PDA-Pt@USPIOs) based on poly acrylic acid-coated ultra-small superparamagnetic iron oxide nanoparticles (PAA@USPIOs) for modulation of the tumor hypoxic microenvironment and magnetic resonance imaging/photoacoustic imaging (MRI/PAI) guided radio-chemotherapy of tumors. The thick PAA coating on the USPIOs allowed highly efficient cisplatin loading by complexing the carboxylic groups on PAA with activated cisplatin. A subsequent thin layer of polydopamine (PDA) encapsulation following drug loading provided a means of further surface functionalization; it endowed the particles with photo-thermal properties but did not impede release of the drug or iron ions. GE11-PDA-Pt@USPIOs had high specificity for EGFR-positive tumor cells, could catalyze decomposition of H2 O2 to oxygen and exhibited radio-chemo synergetic therapeutic effects under hypothermia conditions in vitro . Once administered intravenously, MRI and PA imaging revealed that the probes were able to accumulate in tumors with high efficiency; this relieved the tumor hypoxic conditions, sensitizing the tumors to radiation therapy. As a result, radio-chemo combination therapy significantly inhibited tumor growth. Our study illustrates for the first time that USPIOs can relieve tumor hypoxia and that GE11-PDA-Pt@USPIOs are highly effective for radio-chemotherapy of EGFR-positive tumors.